2018
DOI: 10.1111/jopr.13006
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Biomonitoring of Dental Technicians: A Cross‐Sectional Study

Abstract: Purpose This is a cross‐sectional study to assess the incidence of micronuclei and other nuclear morphological changes in buccal epithelial cells of dental technicians. Materials and Methods The study was conducted on 45 dental technicians versus 2 control groups: 50 dentists and 50 dental assistants. DNA damage was analyzed in exfoliated buccal mucosa cells by micronucleus assay. The differences in the frequency of detected types of cytogenetic damage between experimental groups were analyzed by applying 2‐wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Epithelial cells are the first line of defense for the oral mucosa and thus may be the first to show genotoxic damage [2]. The micronucleus test (MN) using cells exfoliated from the oral epithelium is a method widely used to assess damage to deoxyribonucleic acid (DNA), genotoxicity and genomic instability, and various nuclear abnormalities serve as biomarkers of alterations in cytokinesis or cell death, facilitating assessment of the biocompatibility of specific materials and any pathologic conditions that may arise [3][4][5]. It has recently been recognized that metals used in orthodontic appliances may exert toxic effects on cells through direct and prolonged contact with oral tissues and metal corrosion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells are the first line of defense for the oral mucosa and thus may be the first to show genotoxic damage [2]. The micronucleus test (MN) using cells exfoliated from the oral epithelium is a method widely used to assess damage to deoxyribonucleic acid (DNA), genotoxicity and genomic instability, and various nuclear abnormalities serve as biomarkers of alterations in cytokinesis or cell death, facilitating assessment of the biocompatibility of specific materials and any pathologic conditions that may arise [3][4][5]. It has recently been recognized that metals used in orthodontic appliances may exert toxic effects on cells through direct and prolonged contact with oral tissues and metal corrosion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental and epidemiological research has shown the latent health risks of metal, acrylic and ceramic powder. (Choël, Grosgogeat, Bourgeois, & Descotes, 1999;Hariyani, Berniyanti, & Setyowati, 2015;Tadin et al, 2019). Besides, studies show that fine particle-sized dust (5µm and below) is spread into the working environment during the dental prosthesis production process (Arsal Yıldırım & Pekey, 2018;Hu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%